Peningkatan Ketahanan Korosi Pada Material Biomedik Plat Penyambung Tulang SS 304 Dengan Gabungan Metode Shot peening dan Electroplating Ni-Cr - Sunardi Sunardi; Priyo Tri Iswanto; Mudjijana Mudjijana (Semesta Teknika, 2015)
Stainless steel (SS) 304 is widely used as biomedical materials because of its lower cost and its availability. However its corrosion resistance is lower than that of the SS 316L. The purpose of this study is to determine the influence of the combination surface treatment i.e. shot peening treatment and electroplating Ni-Cr on the corrosion resistance in simulated body fluid (SBF) of SS 304 material. The shot peening treatments were carried out using a variable period of 5, 15 and 30 minutes. Diameter steel balls of 0.6 mm with a hardness of 40-50 HRc, was applied. Pressure compressor was maintained in the range of 6 -7 kg / cm2 with nozzle diameter and the distance between nozzle and the specimen of 5 mm and 10 cm respectively. After shot peening process, the specimens were nickel-electroplated using a voltage of 2 V at current of 0.03 A with the distance between the electrode of 4 cm for 15 minutes. After nickel-electroplated process the specimens were chrome-electroplated using a voltage of 4.5 V at current 0.3 A with the distance between the electrode of 15 cm for 5 minutes. The specimen was then tested its corrosion rate in the test medium SBF using Galvanostat M 273 in the range of -20 mV s / d 20 mV. The corrosion test results show that SS 316L and SS 304 without treatment have corrosion rate respectively 1.212 X 10-3 mm / year and 4,003 x 10-3 mm / year. Which means that corrosion rate of SS 304 is 333% higher than SS 316L. The corrosion rate after treatment shot peening 5, 15 and 30 minutes followed by Ni-Cr electroplating is respectively 2.121 x 10-3 mm / year, 0.554 x 10-3 mm / year and 0 mm / year (not detected by the measurement instrument).